Lavagem de dinheiro e paraísos fiscais: impactos anti-desenvolvimentistas de uma economia sombria - Martins, Fabiano Emidio de Lucena (2015)
Money laundering is a criminological phenomenon consolidated by the deregulation of financial markets, becoming a worldwide primary concern in the last decade of the twentieth century, and, more sharply, after the terrorist attacks of September 11, 2001. In parallel, the consolidation of offshore jurisdictions as an apparently natural phenomenon of market liberalization, allowed, in a perverse symbiosis between money laundering and tax havens, the establishment of what we call dark economy: an economically autonomous and independent microcosm accessible to a minority wealthy, governed by its own rules of maximizing profits at any cost. The dark economy is fueled by colossal illicit financial flows coming from drug trafficking, kleptocrats, terrorists, fraudsters and unsound business. Estimates point out that half of global money supply transit through the offshore world. Poor and developing countries, often oblivious to this reality, have become in recent years, mainly because of the warmth of their systems and control mechanisms, important providers of dark economy. By becoming addressed to massive capital flight from poor and developing countries, the dark economy captures essential resources to poverty eradication, productive investment and the implementation of infrastructure necessary to economical growth of damaged countries, demanding, thereby, a renewed financial sacrifice to balance the public accounts, with unavoidable consequences on increasing the tax and regulatory rigor and greater financial oppression of the vast majority submitted to the formal economy. Faced with this panorama, this paper aims to explain which are the anti-development effects of the dark economy, addressing how the sneaky allocation of financial resources on a large scale in tax havens affects people's lives and how Brazil is within that context.